Bubble Bursting and Drainage Characteristics at the Free Surface of a Liquid Pool with an Aerosol. (16th October 2020) - Yu, Xiang; Gu, Haifeng; Yin, Weikai; Sun, Qingyang
Abstract : When nuclear reactor accidents such as steam generator pipe ruptures or core melting occur, radioactive aerosols will remain in the liquid pools. Bubbles may be generated by boiling or gas injection. Film droplets produced by bubble bursts may entrain radioactive aerosols from the liquid to the air. This long-lasting behavior can produce a considerable amount of aerosols. To evaluate radioactive source terms, many physical quantities related to bubble bursting need to be determined, such as bubble burst position, bubble lifetime, cap film roll-up velocity, and cap film thickness, which are very important parameters that influence the releasing of radioactive aerosols. In this research, the phenomenon of bubble bursting was investigated by visualization. The above parameters were measured. We obtained the lifetime distribution of bubbles under different conditions, and we found that the addition of an aerosol increased the lifetime of the bubbles. By comparing the bubble lifetime to the roll-up velocity and cap thickness, we showed that the increase of the liquid temperature thickened the cap at rupture and the increase of the air temperature thinned the cap. The addition of an aerosol increased the film roll-up velocity.